2003
DOI: 10.1128/jcm.41.7.3344-3347.2003
|View full text |Cite
|
Sign up to set email alerts
|

Strain Variation among Bordetella pertussis Isolates from Québec and Alberta Provinces of Canada from 1985 to 1994

Abstract: Pulsed-field gel electrophoresis and gene typing were able to differentiate among 3,597 Bordetella pertussis isolates circulating in Alberta and Québec Provinces, Canada, from 1985 to 1994 and distinguish them from the strains used in vaccine production. This study provides a baseline for continued surveillance of prevalent and emerging strains of B. pertussis in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(20 reference statements)
2
28
0
Order By: Relevance
“…Recent Dutch isolates were shown to be distinguishable from strains that had been used for the production of vaccines. These same findings were reproduced in many other countries (10,12,14,22,29). Acellular pertussis vaccines were introduced nationwide in Sweden in 1996, 17 years after the withdrawal of whole-cell pertussis vaccine from the childhood immunization schedule (20).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Recent Dutch isolates were shown to be distinguishable from strains that had been used for the production of vaccines. These same findings were reproduced in many other countries (10,12,14,22,29). Acellular pertussis vaccines were introduced nationwide in Sweden in 1996, 17 years after the withdrawal of whole-cell pertussis vaccine from the childhood immunization schedule (20).…”
supporting
confidence: 54%
“…Based on the profiles obtained with each of these two enzymes, Weber et al (29) identified six main groups of B. pertussis, i.e., groups I, II, III, IV␣, IV␤, and V. Reference strains were recommended for strain characterization at the group level (18,29). Many recent studies have put forward the idea of a one-enzyme system, primarily using XbaI (4,5,7,14,22,24). In many of these studies, references to internationally available type strains were lacking (4,5,7,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this resurgence was that the circulating B. pertussis population consisted of strains that were antigenically distinct from the vaccine strains (Mooi et al, 1998). Subsequent studies have reported allelic variation in these two markers in Finland, the UK, Poland, the USA and Canada Cassiday et al, 2000;Fry et al, 2001;Gzyl et al, 2002;Peppler et al, 2003). Additional targets under presumed selective pressure were examined for nucleotide sequence variation by , including other genes encoding proteins used as acellular vaccine (ACV) components and other surface-associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Infants too young to be fully immunized have become the most vulnerable group at highest risk for severe clinical disease, whereas adolescents and adults, previously protected, have become populations susceptible to mild disease (Figure 1) [28,29]. Since the 1990s, a steady increase in the number of pertussis cases was observed in various countries with successful and long-lasting vaccination programs, such as Argentina, Finland, Norway, Spain, Switzerland, Israel, Canada, Australia, the USA and The Netherlands [30][31][32][33][34]. In these countries, different types of pertussis vaccines were being used with proven efficacy in clinical trials.…”
Section: Resurgence Of Pertussismentioning
confidence: 99%